Penggunaan Media Pembelajaran Geometri Berbasis Etnomatematika - Sumiyati, Wiwin; Netriwati, Netriwati; Rakhmawati, Rosida (Desimal: Jurnal Matematika, 2018)
Finding out the influence of learning geometry using ethnomathematics-based learning media for critical thinking ability (critical thinking) is the purpose of this study. This research is experimental research with quantitative research method. Using the posttest-only design in this study. Its population is the control and experimental class. Test methods, documentation and observation interviews are the data collection techniques used. The way is the PowerPoint 2016 media for the experimental group and conventional learning for the control group with. The result is that the differences occur between the apart media and the learning of ethnomathematics that cannot be media learning (conventional). The average experimental value of 86.57 with a variance of 77.57 while the average control value of 77.33 with a variance of 133.50, obtained t count of 3.138, with ttable of 2.011. Based on hypothesis test that with significance level α = 0,05 hence can be concluded there is the influence of media of learning of geometry based on ethnomathematics to students critical thinking ability of mathematical.